2015
DOI: 10.11648/j.ejb.20150306.12
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Spectroscopic and Thermal Characterization of Biofield Treated Fish Peptone

Abstract: Abstract:The by-products of industrially processed fish are enzymatically converted into fish protein isolates and hydrolysates having a wide biological activity and nutritional properties. However, the heat processing may cause their thermal denaturation thereby causing the conformational changes in them. The present study utilized the strategy of biofield energy treatment and analysed its impact on various properties of the fish peptone as compared to the untreated (control) sample. The fish peptone sample w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Thermal characterizations (TGA and DSC) were performed in this study, with the purpose of obtaining evidence of the presence of carbon and nitrogen sources on the PCL matrix by observing the mass degradation vs. temperature increment (TGA) and key temperature fluctuations (DSC) [ 19 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. The calculated critical degradation temperature (TGA) is close to our reported decomposition temperature (DSC) of around ~380–390 °C.…”
Section: Discussionmentioning
confidence: 99%
“…Thermal characterizations (TGA and DSC) were performed in this study, with the purpose of obtaining evidence of the presence of carbon and nitrogen sources on the PCL matrix by observing the mass degradation vs. temperature increment (TGA) and key temperature fluctuations (DSC) [ 19 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. The calculated critical degradation temperature (TGA) is close to our reported decomposition temperature (DSC) of around ~380–390 °C.…”
Section: Discussionmentioning
confidence: 99%
“…The Trivedi Effect ® (Biofield Energy Treatment) has been reported worldwide with significant outcomes in many reasearch fields. Widespread studies were reported in case of cancer research [30,31], altered antimicrobial sensitivity against pathogenic microbes was reported in microbiology [32][33][34][35], genetics [36,37], altered physiochemical properties of important compounds in pharmaceutical science [38][39][40][41][42], improved crop productivity and quality of crops in agricultural science [43][44][45], and in changing the structure of the atom in relation to various polymers, ceramics, metals and chemicals in materials science [46][47][48], and much more.…”
Section: Discussionmentioning
confidence: 99%
“…The Trivedi Effect ® has improved the overall productivity of crops in agriculture and livestock [13][14][15][16], positive impact on cancer [17,18], and altered characteristics features of microbes in the field of microbiology [19][20][21]. It also altered the structural, physical, and thermal properties of several metals and ceramics [22][23][24], cause chromosomal changes in microbes [25,26], and improved various nutraceutical compounds in the areas of nutraceuticals [27,28] and biotechnology [29][30][31]…”
Section: Introductionmentioning
confidence: 99%